2011
DOI: 10.1007/s12257-011-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and microencapsulation of a probiotic in alginate-chitosan capsules improves survival in simulated gastrointestinal conditions

Abstract: The aim of the present study was to focus on the impact of two different methods and the effects of cryoprotectants on the survival of a probiotic bacterium, Streptococcus phocae PI80, during storage. For the protection of freeze dried cells, the optimal storage conditions were determined with a high survival rate. After the freeze drying process, all cryoprotectants exhibited a protective effect on cell viability at all storage temperatures. High relative cell viability was observed when cells were incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 37 publications
(50 reference statements)
0
46
0
2
Order By: Relevance
“…Chitosan was also employed as a cladding material (Kanmani et al, 2011). Gelatin was used as a substrate in the formation of the microcapsules.…”
Section: Preparation Of the Chinese Herbal Microcapsules Preparation mentioning
confidence: 99%
“…Chitosan was also employed as a cladding material (Kanmani et al, 2011). Gelatin was used as a substrate in the formation of the microcapsules.…”
Section: Preparation Of the Chinese Herbal Microcapsules Preparation mentioning
confidence: 99%
“…Encapsulation technology has been proved to be one of the most effective ways to protect probiotics during processing and subsequent storage (Kanmani et al, 2011;Liserre, Ines-Re, & Franco, 2007). Furthermore, encapsulation systems with control-released ability can deliver probiotics to a specific target and release them at required time (Burgain, Gaiani, Linder, & Scher, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A 2 % of D-glucose was added to the starting sodium alginate solution, since Corcoran and co-workers (Corcoran et al 2005) have demonstrated an enhancement of the survival of lactobacilli in acid environment that represents one of the main stress conditions in the gastrointestinal tract. Moreover, the sugar supplemented in the alginate micro-particle preparation could improve the long-term viability of encapsulated probiotic by acting as cryo-preserving agent during storage under refrigerated conditions, as demonstrated by Priya et al (2011;Kanmani et al 2011). The formulation was completed by the addition of the β-glucan Pleuran, as additive (or Effect of microencapsulated and non-microencapsulated probiotic strains on the potential antioxidant of HT-29 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most recent studies exploit alginate-chitosan microcapsules for entrapping probiotic bacteria, as reported by Kanmani et al 2011, few studies are reported concerning the effect of this kind of microencapsulation on the bacterial viability and activity on intestinal cell lines during in vitro tests. The main body district in which probiotics exert their positive health effect is the intestine due to their ability to colonise and repopulate the gut microbiota environment (Gueimonde and Salminen 2005;Nissen et al 2009).…”
Section: Introductionmentioning
confidence: 99%